(-)-Epigallocatechin-3-gallate (EGCG) modulates polarized macrophages to suppress M1 phenotype and promote M2 polarization in vitro and in vivo. (December 2021) - Hu, Yaozhong; Gu, Jiaxin; Lin, Jing; Wang, Yi; Yang, Feier; Yin, Jia; Yu, Zhenting; Wu, Sihao; Lv, Huan; Ji, Xuemeng; Wang, Shuo
Graphical abstract: Highlights: Effect of EGCG on macrophage polarization has been thoroughly confirmed. The suppression of M1 polarization after EGCG treatment was observed. The promotion of M2 macrophages after EGCG treatment has been confirmed. Abstract: The intervention of EGCG on M1/M2 macrophage polarization was still unclear and should be studied comprehensively. In this context, the intervention of EGCG on macrophage polarization has been investigated to reveal that EGCG promoted M2 polarization of RAW264.7 upon treating with EGCG. A significant inhibitory effect of EGCG on M1 polarization was observed upon stimulating with LPS and IFN-γ. The expression of macrophage phenotype related marker genes (iNOS, COX-2, IL-1β for M1; Arg-1, Ym-1, IL-10 for M2) demonstrated the suppression of M1 polarization and the promotion of M2 polarization in liver, colon, spleen, and brain. Further analysis against peritoneal macrophages verified the increased M2 phenotypes and decreased M1 macrophages, and the similar variation in liver were confirmed by immunohistochemistry (IHC). No significant variation of spleen macrophages was observed with the general macrophages in declined tendency. Bio-distribution of EGCG and its metabolites (EGC, GA) in different organs has been further determined.